Study of Role of Iron Deficiency Anaemia in Febrile Seizures in Children in a Tertiary Care Centre - Sreenivasa, Bheema Naik; Kumar, Gowripura Visweswaraiah; Manjunatha, Bheema Naik (Journal of Nepal Paediatric Society, 2016)
Introduction: The world health organization estimates that anaemia largely caused by iron deficiency, affecting between 500 million and two billion people worldwide. Considering the age prevalence of iron deficiency anaemia and febrile convulsion which are the same, the role of iron in the metabolism of neurotransmitter and some enzymes, the function of hemoglobin in conveying oxygen to the brain and since fever can exacerbate symptoms that result from anaemia, a relationship between iron deficiency anaemia and febrile convulsions is probable. Some studies have suggested iron deficiency as a predisposing factor for febrile seizures. We designed this case control study to evaluate the relationship between iron deficiency anaemia and febrile convulsions. The objective of this study was to study the role of iron deficiency as a risk factor for febrile seizures. Materials and Methods: Hundred cases and 100 controls were included in the study. Cases were children of age group six months to six years presenting with febrile seizures. Controls were children of same age group presenting with febrile illness but without any seizures. After informed consent, detailed history was taken and clinical examination done in both cases and controls and blood investigations were done to diagnose iron deficiency anemia. Two groups were matched for age and sex. In all children hemoglobin (Hb) level, mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), red cell distribution width (RDW) and plasma ferritin (PF) were determined and the data collected were analyzed statistically. Results: The mean PF was significantly lower in cases compared to controls (p=0.000) and RDW was significantly higher in cases compared to controls (p=0.00). The mean Hb%, MCV, MCH are lower in cases compared to controls but it was statistically not significant. Concluson: Iron deficiency is a significant risk factor for febrile seizures in children of age group six months to six years. Early detection and timely correction of iron deficiency may be helpful for prevention of febrile seizures in children. J Nepal Paediatr Soc 2015;35(2):148-151